Kesadaran Beragama pada Masa Remaja - Ervien Zuroidah (Maddah: Journal of Advanced Da'wah Management Research, 2022)
Religious awareness means that an adherent of a religion lives, internalize and integrate religious values ​​into his personality so that it will become part of his heart and personality that will affect his attitudes and behavior in social life. The appreciation of religious norms includes the norms of human relations with God, relationship with society and the environment. A life based on religious values ​​will foster a healthy personality which contains elements of religion and a fairly firm faith. And vice versa, people whose souls are shaken and far from religion, the individual will get angry easily, hopeless, disappointed, and not being able to adapt well to the surrounding environment so that it will tend to be a problem for others. And especially for teenagers who are still unstable, then religious awareness needs to be built in them.